Integrating the Triple Bottom Line into Csr Communication Strategies: The Case of D’botanica Bandung Mall’s Tree Distribution Initiative - Lathifah, Nisa; Dewi, Anggia Puspita; Sugiarta, Nugraha; Sadiyyah, Zulfanida Nurul (Sinergi International Journal of Communication Sciences, 2025)
D’Botanica Bandung Mall implemented a Corporate Social Responsibility (CSR) program by distributing 2,600 tree seedlings to SMAN 9 Bandung. The initiative was carried out using the Triple Bottom Line framework, which in this study was applied to examine how D’Botanica Bandung Mall integrates economic, environmental, and social sustainability dimensions. This study employed a qualitative case study approach, with data collected through interviews, observations, and documentation involving both mall representatives and the school community. The findings reveal that the program indirectly improved the mall’s image, reflecting its profit dimension and strengthened its branding as a green mall, potentially increasing visitor awareness. From the Planet perspective, the initiative contributed to school greening efforts and supported the sustainability of the urban ecosystem. Meanwhile, from the People dimension, the program fostered school community engagement while also providing environmental awareness education.